2023
DOI: 10.1002/adhm.202203245
|View full text |Cite
|
Sign up to set email alerts
|

A Biomimetic Lubricating Nanosystem with Responsive Drug Release for Osteoarthritis Synergistic Therapy

Abstract: Osteoarthritis (OA) is associated with lubrication failure of articular cartilage and severe inflammatory response of joint capsule. Synergistic therapy combining joint lubrication and anti-inflammation emerges as a novel treatment of OA. In this study, bioinspired by ultralow friction of natural articular synovial fluid and mussel adhesion chemistry, a biomimetic nanosystem with dual functions of enhanced lubrication and stimuli-responsive drug release is developed. A dopamine mediated strategy realizes one s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 49 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…The detailed C 1s spectrum in Figure 3f showed sp 2 (C�C) at a binding energy of 284.4 eV, sp (C� C) at 285.0 eV, C−O at 286.5 eV, and C�O at 288.0 eV. 43,44 The small amount of C−O and C�O bonds might be due to the oxygen in the air being adsorbed on the surface of GDY, and it was also possible that the oxygen chemically reacted with some of the exposed terminal alkyne bonds. 45 EDS mapping results in Figure 3g showed that higher proportions of Si, O, and C were observed, and small amounts of Fe and Cu were also detected.…”
Section: Resultsmentioning
confidence: 99%
“…The detailed C 1s spectrum in Figure 3f showed sp 2 (C�C) at a binding energy of 284.4 eV, sp (C� C) at 285.0 eV, C−O at 286.5 eV, and C�O at 288.0 eV. 43,44 The small amount of C−O and C�O bonds might be due to the oxygen in the air being adsorbed on the surface of GDY, and it was also possible that the oxygen chemically reacted with some of the exposed terminal alkyne bonds. 45 EDS mapping results in Figure 3g showed that higher proportions of Si, O, and C were observed, and small amounts of Fe and Cu were also detected.…”
Section: Resultsmentioning
confidence: 99%
“…[39] At present, synergistic therapy has been reported to overcome the shortcomings of monotherapy in diseases. [69] Taking advantage of BMP6, in this study, a novel co-loading nanoplatform called UIO-66-NH 2 @GYY4137@BMP6 was developed using BMP6 recombinant active protein to strengthen the antioxidation and proangiogenic functions. Then we found that UIO-66-NH 2 @GYY4137@BMP6 further magnified the activating ability of Hippo-YAP/TAZ signaling pathway, which plays a vital role in tissue repair and organ regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Lubrication dysfunction of articular cartilage is consequently considered to determine the onset of OA and is followed by synovium inflammation that then promotes the pathological progress of OA. With respect to the complex and multifactorial characteristics of OA, , therapeutic strategies that only consider lubrication or anti-inflammation are usually ineffective. Additionally, as the global population increasingly ages and as the degradation of articular cartilage is irreversible when OA occurs, the prevention of OA is urgently required, and this may be achieved by a combination of maintaining lubrication and anti-inflammatory conditions. …”
Section: Introductionmentioning
confidence: 99%